Ecofisiologia de plantas nativas e cultivadas e parâmetros físicos e químicos do ambiente em sistemas agroflorestais no semiárido cearense - Mendes, Marlete Moreira de Sousa (2013)
Studies show that when the trees are placed on culture systems, the environmental characteristics are positively influenced and productivity of the cultivation may or may not be positively impacted. However, most of these studies focused environments with good moisture conditions. The comparative study of agroforestry and other forms of land use generates information linking productivity and environmental preservation, especially in ecosystems with low water availability. The aim of this study was to evaluate the effects of the system agrosilvopastoral (AGP) on soil chemical and physical environment properties and on physiology, development and nutrient content of native and cultivated plants, taking as reference areas of traditional cultivation system (TR) and secondary forest (MS). The research was conducted at sites belonging to Embrapa Sheep and Goats, Sobral-CE, in the period between February and September 2011. We evaluated physical parameters of the environment (air humidity, soil moisture, soil and air temperatures, photosynthetically active radiation, wind speed and rainfall) recorded using two weather stations installed in the AGP and the MS, chemical parameters of the soil (Nt, P, K+, Ca2+, Mg2+, Na+, pH, organic carbon, Fe, Zn, Cu and Mn), corn (Zea mays) and pau-branco (Cordia oncocalyx) ecophysiological (specific leaf area, chlorophyll content, photosynthesis, transpiration, stomatal conductance, water use efficiency, water potential), besides differentiate areas of water uptake by plants by stable isotope. An experiment was also developed in a greenhouse to evaluate the occurrence of competition for water between maize and pau-branco developing alone or in combination. Corn grown in AGP was compared with plants grown under traditional methods (after slash-and-burn vegetation) and presented a further development in the AGP if it was not under the canopy of pau-branco, which promoted competition, leading to a reduction in physiological processes and development of corn to 1 m, 2 m and 3 m away from the stem of pau-branco (Chapter 1). The experiment in the greenhouse showed that corn has its physiological parameters changed both by the association and by level of irrigation, with an impact on development. Thus, the association promotes competition between maize and pau-branco much as 100% to 50% of field capacity, however, corn is the most affected species (Chapter 2). The 10 pau-branco tress in AGP showed greater resistance to dry than MS plants, since they were able to maintain the green leaves longer and maintain higher transpiration rates, stomatal conductance and photosynthesis, and greater water content in the apical leaves in dry period, when the gravimetric water content of soil was lower in the AGP than the MS (Chapter 3). The stable isotopes analyzes revealed that corn and pau-branco in AGP system preferentially take up water from soil depths greater than 20 cm, which lead to a reduction in soil moisture at 30-50 cm depth. In MS paubranco sources water from more superficial soil layers, up to 30 cm depth (Chapter 4). Photosynthesis in pau-branco, during the dry season, was less dependent on environmental factors in MS than in AGP, suggesting that plants in the AGP have developed strategies which resulted in higher net carbon assimilation (Chapter 5), with this, the trees in AGP showed a high level in some nutrients, reflecting the better quality soil chemistry of this system (Chapter 6). Given these results, it is understood that AGP is a system suitable conditions semiarid Northeastern, it may enhance the development of trees and maize, since this is not shaded by the canopy, and of the soil, although some climatic variables are more extreme in the system.